Cost of transformation: a measure on matchings - Burak Can; Mohsen Pourpouneh; Ton Storcken (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2020)
This paper constructs a normative framework to quantify the difference (distance) between outcomes of market mechanisms in matching markets. We investigate the "cost of transformation" from one market mechanism to another, based on the differences in the outputs of these mechanisms, i.e., the matchings. Several conditions are introduced to ensure that this cost reflects the welfare effect of the transformation on individuals. We find a class of measures called scaled Borda measures, which is characterized by these conditions. Several possible applications of these measures in different markets are also discussed, such as measuring how unstable, how unfair, or how inefficient a mechanism (or a matching) is.
Keywords: C78; D61; D63; 330; matching markets; distance function; metrics; cost of stability